1995
DOI: 10.1007/bf02019054
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cost-effective timing of cranial ultrasound screening in low-birth-weight infants

Abstract: Our aim in this study was to determine whether delaying the initial screening cranial ultrasound on infants of low birth weight until the 2nd week of life affects clinical diagnosis and cost of patient care. Data were reviewed on all premature infants of less than 33 weeks gestation or less than 1500 g birth weight admitted to the Neonatal Intensive Care Unit between January 1989 and August 1992. Babies admitted before August 1991 were screened on day 4 or 5 with a second scan frequently performed on day 14; b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…Moderate and severe HIE were significant risk factors of CP, as were grade 3 and 4 IVH. Ultrasound abnormalities associated with CP included PVL, grade 3 and 4 IVH, encephalomalacia, meningitis, hydrocephalus, and ventriculomegaly, which were similar to previous findings in the published literature.1 [3][4][5][6][7][8][9][10][11][12][13][14][15] The diagnosis of CP is straightforward in cases of severe CP or in older children. It is difficult to accurately diagnose CP in the first 6 months of life, in milder cases, or in cases of isolated motor delay.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Moderate and severe HIE were significant risk factors of CP, as were grade 3 and 4 IVH. Ultrasound abnormalities associated with CP included PVL, grade 3 and 4 IVH, encephalomalacia, meningitis, hydrocephalus, and ventriculomegaly, which were similar to previous findings in the published literature.1 [3][4][5][6][7][8][9][10][11][12][13][14][15] The diagnosis of CP is straightforward in cases of severe CP or in older children. It is difficult to accurately diagnose CP in the first 6 months of life, in milder cases, or in cases of isolated motor delay.…”
Section: Discussionsupporting
confidence: 69%
“…This result concurs with previous studies reporting that ultrasound abnormalities, especially grade 3 and 4 intraventricular hemorrhage (IVH), periventricular leukomalacia (PVL), and ventriculomegaly were associated with CP or other abnormalities of motor development. [13][14][15] All subjects with moderate and severe HIE (n=7) had CP, a significant difference from the proportion of CP in subjects with no or mild HIE (P<0.001). Similarly, previous studies reported that HIE, particularly in term infants, causes tissue damage in the form of PVL, focal and multifocal ischemia, and cerebral tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…When BW was Ͻ1,000 grams, severe IVH was detected in 10 (77%) of 13 infants on days 1 to 5; 13 (100%) of 13 cases of severe IVH were detected on day 28. In a study designed to assess changes in US findings across time, 42 144 infants with BW of Ͻ1,500 grams or GA of Ͻ33 weeks underwent US between days 1 and 7 and then between days 10 and 14. Fifteen infants (10%) had significant changes in US findings from the first to the second scan.…”
Section: Whichmentioning
confidence: 99%
“…21,22 Neonatal centers in developed countries regularly perform cranial ultrasound scan with time protocol based on birth weight. 17,23,24 American Academy of Neurology has outlined a protocol to evaluate preterm brain. 25 Our hospital had limited facilities for delivering high care to high-risk infants, including imaging facilities.…”
Section: Resultsmentioning
confidence: 99%